2011
DOI: 10.1128/cvi.05005-11
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae Alpha-Like Protein 1 Possesses Both Cross-Reacting and Alp1-Specific Epitopes

Abstract: Most isolates of group B streptococci (GBS) express an alpha-like protein (Alp), C␣ (encoded by bca), Alp1 (also called epsilon; alp1), Alp2 (alp2), Alp3 (alp3), Alp4 (alp4), or R4/Rib (rib). These proteins are chimeras with a mosaic structure and with antigenic determinants with variable immunological crossreactivities between the Alps, including Alp1 and C␣ cross-reactivity. This study focused on antigenic domains of Alp1, studied by using rabbit antisera in immunofluorescence, Western blotting, and enzymeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Furthermore, smaller amounts of antibodies against alpha and Rib proteins, present in the host, have also been reported to be associated with a higher incidence of disease (67). Therefore, alpha-like proteins have been considered potential antigens for the development of a vaccine against GBS (67)(68)(69). Here, we observed a 4-fold increase in the expression of the rib gene following incubation in whole human blood, leading to a high level of expression of this immunogenic protein.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, smaller amounts of antibodies against alpha and Rib proteins, present in the host, have also been reported to be associated with a higher incidence of disease (67). Therefore, alpha-like proteins have been considered potential antigens for the development of a vaccine against GBS (67)(68)(69). Here, we observed a 4-fold increase in the expression of the rib gene following incubation in whole human blood, leading to a high level of expression of this immunogenic protein.…”
Section: Discussionsupporting
confidence: 52%
“…For example, immunization with a C␣ with as many as 16 repeats failed to induce anti-N-terminalregion antibodies and also affected the protective activity of the antibodies elicited (19,22,29). Similar observations have been made in our laboratory (31). Immunization with purified recombinant C␣ N terminus or the N terminus as part of a fusion protein resulted in a strong antibody response when the immunogenicity of the C␣ N terminus was not suppressed by multiple C-terminal repeats (22,29).…”
supporting
confidence: 67%
“…AAJP00000000) and sequences from the strain A909 bca (GenBank accession no. M97256) were aligned, it was found that the Alp1 and C␣ repeats were virtually identical (31). This explains why the C-terminal regions from Alp1 and C␣ behaved immunologically as two identical antigens, including the ability of both repeat regions to bind a monoclonal antibody raised against the C␣ from A909 (31).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…However, the immunological uniqueness of the proteins Z1, Z2, and R3, indicated by the data of this and earlier studies (9,11), suggests that it may become possible to develop molecular typing methods for specific detection of each of the protein-encoding genes, perhaps by including primer sets for the genes in a multiplex PCR. This prediction is based on data which indicate that at least some strain-variable GBS genes which can be identified by gene-specific PCR often encode proteins which possess protein-specific epitopes (20,21,28,29). Knowledge of the usefulness of Z1, Z2, and R3 determination in GBS serotyping is sparse and unknown for GBS from most areas of the world (9)(10)(11)(12)30).…”
Section: Discussionmentioning
confidence: 99%